1999
DOI: 10.1038/22678
|View full text |Cite
|
Sign up to set email alerts
|

Diamond formation from mantle carbonate fluids

Abstract: A fter the accident at the Chernobyl nuclear reactor in 1986, the concentration of radioactive caesium ( 134 Cs and 137 Cs) in fish was expected to decline rapidly. The estimated ecological half-life (the time needed to reduce the average caesium concentration by 50%) was 0.3 to 4.6 years 1,2 . Since 1986, we have measured radiocaesium in brown trout (Salmo trutta) and Arctic charr (Salvelinus alpinus), both of which are widely eaten in Scandinavia, in a lake contaminated by Chernobyl fallout 3,4 . We have mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(102 citation statements)
references
References 0 publications
3
97
1
1
Order By: Relevance
“…High solubility of magnesiowustite in this carbonate melt produces a relatively low-melting temperature. The minimum temperature of nucleation and growth of diamonds in the carbonate melt, established in this study, is lower than that previously found for dry alkaline-carbonate melts (55).…”
Section: Significancecontrasting
confidence: 47%
“…High solubility of magnesiowustite in this carbonate melt produces a relatively low-melting temperature. The minimum temperature of nucleation and growth of diamonds in the carbonate melt, established in this study, is lower than that previously found for dry alkaline-carbonate melts (55).…”
Section: Significancecontrasting
confidence: 47%
“…Diamond crystallization in the system K 2 CO 3 /H 2 O/CO 2 /C was studied earlier at 5.7 GPa and 1,150-1,420°C with relatively low concentrations of water (59,60). However, to make a correct comparison of different compositions in the system KCl/K 2 CO 3 / H 2 O/C at equal P,t, and run duration ( ), we performed additional experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Sunagawa (1990Sunagawa ( , 1997 identified three kinetic-morphologic fields, including a region at low driving force and/or rapid kinetics where highly perfect crystals grow, a region at high driving force and/or slow kinetics where highly imperfect growth is expected to occur, and a region in between, where hopper and/or skeletal crystals predominate. Sunagawa considered the kinetic effects to be due to temperature alone, but Kanda (1985) and Pal'yanov et al (1999) showed that the fluid from which diamonds grow (H 2 O and carbonate melt, respectively) can have an important additional effect on kinetics and hence on morphology (H 2 O increases skeletal morphology and carbonate melt yields perfect octahedra). Thus, increasing the driving force for growth and decreasing the kinetics of growth have similar effects on diamond morphology, but the kinetics cannot be simply described in terms of temperature.…”
Section: Some Notes Related To Microdiamond Morphologiesmentioning
confidence: 98%